Mechanistic study of nanoparticlesâsurfactant foam flow in etched glass micro-models - Yekeen, N. (Taylor and Francis Inc., 2018)
This study was conducted in order to identify the pore-level mechanisms controlling the nanoparticlesâsurfactant foams flow process and residual oil mobilization in etched glass micro-models. The dominant mechanism of foam propagation and residual oil mobilization in water-wet system was identified as lamellae division and emulsification of oil, respectively. There was inter-bubble trapping of oil and water, lamellae detaching and collapsing of SDS-foam in the presence of oil in water-wet system and in oil-wet system. The dominant mechanisms of nanoparticlesâsurfactant foam flow and residual oil mobilization in oil-wet system were the generation of pore spanning continuous gas foam. The identified mechanisms were independent of pore geometry. The SiO2-SDS and Al2O3-SDS foams propagate successfully in water-wet and oil-wet systems; foam coalescence was prevented during film stretching due to the adsorption and accumulation of the nanoparticles at the gasâliquid interface of the foam, which increased the filmsâ interfacial viscoelasticity. Â© 2017 Taylor & Francis.